Effects of Boron on the Emergence and Allocation of Metabolic Compounds in Two Herbaceous Cotton Cultivars - Roberta Possas de Souza; Maycon Anderson de Araujo; Lucas Baltazar Longhi; Isabella Fiorini de Carvalho; Bruno Bonadio Cozin; Liliane Santos de Camargos (Plants)
High boron (B) concentrations in the soil can cause toxic effects to plants, so herbaceous cotton (Gossypium hirsutum latifolium Hucth) is a crop sensitive to such stress. Thus, this study aimed to evaluate the emergence, partitioning, and allocation of metabolic compounds of two herbaceous cotton cultivars subjected to B treatments. The experiment was carried out in a greenhouse, under a completely randomized design in a 2 × 4 factorial scheme, using two cultivars and four concentrations of B in the form of boric acid: 0.5 (control), 30, 60, and 120 mg dm−3 B. The increase in the concentration of B in the soil generated a significant toxic effect on the growth and biomass of the cotton plant. Cultivar 1—TMG 50 WS3 obtained greater emergence and shoot growth, while cultivar 2—FM 911 GLTP invested in roots; however, in both cultivars, B remained accumulated in the shoot. There was an increase in amino acids in the roots and a decrease in proteins and phenolic compounds in leaves and cotyledons. It was concluded that the seedlings presented satisfactory emergence up to 60 mg dm−3 B, and that among the cultivars there are distinct responses to B application.